Time use dynamics in paid work and household activities of married women: A panel analysis with household information and regional labour demand - Joachim Merz (Universität Lüneburg, Forschungsinstitut Freie Berufe (FFB), 1992)
The dynamics of multiple time use in paid work and in household activities with housework, child rearing and DIY of married women are analyzed with a two step procedure: the estimation of the participation decision in intertemporal labor force participation strategies (entering, leaving the labor market, permanently employed and not employed) by a multinomial logit approach is followed by a selectivity bias corrected simultaneous hours equations systems (C3SLS) estimation of the determinants of hours supplied in multiple time use activities. Microdata base is the German Socio-Economic Panel with four waves (1984-1987), where information of the household - including the husband's employment situation - is merged with regional economic and local labour demand indicators. – – Die Dynamik multipler Zeitverwendung in Beruf und Haushalt mit Hausarbeit, Kindererziehung und Do-it-yourself-Aktivitäten wird in einer zweistufigen Prozedur analysiert: Der Schätzung der Partizipationsentscheidung in intertemporalen Erwerbsstrategien (Ein- und Austritt aus und in den Arbeitsmarkt, längerfristige Erwerbs- und Nichterwerbstätigkeit) durch einen multinomialen Logit-Ansatz folgt eine selektivitätskorrigierte simultane Schätzung multipler Zeitverwendung (C3SLS). Mikrodatenbasis ist das Sozio-Ökonomische Panel mit vier Wellen (1984-1987), wobei Haushaltsinformationen - inclusive der Beschäftigungssituation des Ehemannes - verknüpft wurden mit regionalen Indikatoren zur ökonomischen Situation und der lokalen Arbeitsnachfrage.
Keywords: D13; J16; J20; J22; J23; 330; Dynamics of multiple time use; market and non-market activities; female labour supply; multiple longitudinal labor and activity supply of married women; panel analysis with regional information; selectivity bias corrected simultaneous equations system estimation of multiple time use; Dynamik multipler Zeitverwendung; Markt- und nichtmarktmäßige Aktivitäten; Arbeitsangebot von Frauen; Multiples Arbeits- und Aktivitätsangebot im Längsschnitt verheirateter Frauen; Panelanalyse mit regionalen Informationen; selektivitätskorrigierte simultane Schätzung multipler Zeitverwendung; Weibliche Arbeitskräfte; Haushaltsproduktion; Zeitverwendung; Deutschland